Optimizing the Enhancement of Dynamic Positioning Operator Competencies on MV. ENA HABITAT DP-II - Cahyono, Dwi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
The Dynamic Positioning (DP) System is essential in modern maritime operations, especially for offshore projects, as it enables vessels to maintain a fixed position and heading without traditional anchoring. A DP Operator plays a critical role in ensuring the system functions effectively, and the success of DP operations largely depends on their competence. Therefore, optimizing operator skills is key to safe and efficient operations. This qualitative study draws on the author’s observations as a DP Operator aboard the MV. ENA HABITAT, as well as relevant literature. It identifies three essential phases of DP offshore operations: pre-operation procedures, on-DP operation, and post-operation or termination. Neglecting any of these stages can disrupt project progress, cause financial losses, or compromise safety. The study also highlights common challenges faced during DP operations on MV. ENA HABITAT DP-II, including sensor failures, thruster issues, system configuration difficulties, harsh environmental conditions, human error, external infrastructure interference, and communication breakdowns. These issues, if unaddressed, can lead to serious incidents. To mitigate these risks, the paper emphasizes enhancing DP Operator capabilities through a range of strategies: accumulating sea time on various vessel types, engaging in advanced simulator training, deepening system knowledge via FMEA (Failure Mode and Effects Analysis) courses, regularly evaluating operations, participating in Continuing Professional Development (CPD), and strengthening non-technical skills such as teamwork and communication.Improving these competencies ensures not only operational success but also the safety and security of both vessel and crew during DP activities.